Pee power urinal – microbial fuel cell technology field trials in the context of sanitation. Issue 2 (20th January 2016) - Ieropoulos, Ioannis Andrea; Stinchcombe, Andrew; Gajda, Iwona; Forbes, Samuel; Merino-Jimenez, Irene; Pasternak, Grzegorz; Sanchez-Herranz, Daniel; Greenman, John
Abstract : This paper reports on the pee power urinal field trials, which are using microbial fuel cells for internal lighting. Abstract : This paper reports on the pee power urinal field trials, which are using microbial fuel cells for internal lighting. The first trial was conducted on Frenchay Campus (UWE, Bristol) from February–May 2015 and demonstrated the feasibility of modular MFCs for lighting, with University staff and students as the users; the next phase of this trial is ongoing. The second trial was carried out during the Glastonbury Music Festival at Worthy Farm, Pilton in June 2015, and demonstrated the capability of the MFCs to reliably generate power for internal lighting, from a large festival audience (∼1000 users per day). The power output recorded for individual MFCs is 1–2 mW, and the power output of one 36-MFC-module, was commensurate of this level of power. Similarly, the real-time electrical output of both the pee power urinals was proportional to the number of MFCs used, subject to temperature and flow rate: the campus urinal consisted of 288 MFCs, generating 75 mW (mean), 160 mW (max) with 400 mW when the lights were connected directly (no supercapacitors); the Glastonbury urinal consisted of 432 MFCs, generating 300 mW (mean), 400 mW (max) with 800 mW when the lights were connected directly (no supercapacitors). The COD removal was >95% for the campus urinal and on average 30% for the Glastonbury urinal. The variance in both power and urine treatment was due to environmental conditions such as temperature and number of users. This is the first time that urinal field trials have demonstrated the feasibility of MFCs for both electricity generation and direct urine treatment. In the context of sanitation and public health, an independent power source utilising waste is essential in terms of both developing and developed world.